Teacher Corrective Oral Feedback in the Classroom - Nasy Inthisone Pfanner (National Research University Higher School of Economics, 2015)
The article reports on a study of teacher corrective oral feedback in Iris Becker Elementary School, a public school serving pupils from kindergarten-5th grade in Dearborn, Michigan. Some researchers claim that teacher corrective oral feedback is beneficial to L2 learning while others discard its merit. This study is an attempt to explore this topic further with young learners. The method used in the study included one classroom observation. The participants included one mainstream classroom teacher and about 25 students. The results show high teacher corrective oral feedback.